Identification of a holin encoded by the Streptomyces aureofaciens phage micro1/6; functional analysis in Escherichia coli system - Farkasovská, J; Godány, A; Vlcek, C (Folia microbiologica, 2004)
An open reading frame encoding an 88 amino acid protein was present downstream of the previously characterized endolysin of Streptomyces aureofaciens phage micro1/6. Structural analysis of its sequence revealed features characteristic for holin. This open reading frame encoding the putative holin was amplified by polymerase chain reaction and cloned into the expression vector pET-21d(+). Synthesis of the holin-like protein resulted in bacterial cell death but not lysis. The holmicro1/6 gene was able to complement the defective lambda S allele in the nonsuppressing Escherichia coli HB101 strain to produce phage progeny, This fact suggests that the proteins encoded by both phage genes have analogous function, i.e. the streptomycete holin induces nonspecific lesions in the cytoplasmic membrane, through which the lambda endolysin gains an access to its substrate, the cell wall. The concomitant expression of both S. aureofaciens holmicro 1/6 and lambda endolysin in E. coli resulted in abrupt cell lysis. This result provided further evidence that the product of holmicro 1/6 gene is a holin.
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; sekvence aminokyselin; Streptomyces aureofaciens; Endopeptidases; endopeptidasy; Cloning, Molecular; Base Sequence; sekvence nukleotidů; Escherichia coli; Viral Proteins; Bacteriophages; Amino Acid Sequence; sekvenční analýza DNA; klonování DNA; bakteriofágy; molekulární sekvence - údaje; virové proteiny; bakteriolýza; Bacteriolysis